A new salinity equation for sound speed instruments. (13th September 2017) - Allen, J. T.; Keen, P. W.; Gardiner, J.; Quartley, M.; Quartley, C.
Abstract: A new equation is presented for the calculation of salinity from triplets of temperature, pressure, and sound speed in marine and estuarine waters. The sixty nine term, sixth order, equation is valid over an environmental range of 0–40°C, 0–6000 dbar, and 0–40 psu. The equation can reproduce a UNESCO speed of sound equation derived reference parameter space to an RMS error of ± 0.0014 psu. The limitation for practical use is the ± 0.05 ms −1 accuracy of the best of the current equations for calculating sound speed. A new reference dataset, either laboratory or in‐situ, is required to match the capabilities of new sound speed measuring instruments.